PENERAPAN INFLUENCER MARKETING TERHADAP SENSITIVITAS HARGA PRODUK (STUDI PADA UMKM KOTA BATURAJA) - Feri , Feri; Munajat, Munajat; Rini Efrianti; Fifian Permata Sari (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of implementing influencer marketing strategies on product price sensitivity in MSMEs in Baturaja City, with a case study on Aneka Kue & Kemplang Syafira. In this study, price sensitivity is defined as the level of consumer response to changes in the price of products offered. Data were obtained through a survey of 40 respondents and analyzed using statistical tests, especially the t-test, to measure the relationship between influencer marketing variables and price sensitivity. The results of the study indicate that the implementation of influencer marketing has a significant effect on the price sensitivity of MSME products. Influencer credibility, content quality, and the level of audience interaction with the promoted content play an important role in building product value perceptions. Influencer marketing has been shown to reduce price sensitivity by shifting consumer focus from price to perceived product value. In the long term, this strategy can help MSMEs strengthen their market position by increasing customer loyalty, brand awareness, and consumer retention. However, to ensure the sustainability of its impact, longitudinal analysis and combination with other marketing strategies are needed. This study contributes to the development of MSME marketing strategies, especially in the increasingly competitive digital era.